Concentration‐dependent effects of dichloroacetate in type 2 diabetic hearts assessed by hyperpolarized [1‐13C]‐pyruvate magnetic resonance imaging. (20th January 2022) - Hansen, Esben Søvsø Szocska; Bertelsen, Lotte Bonde; Bøgh, Nikolaj; Miller, Jack; Wohlfart, Paulus; Ringgaard, Steffen; Laustsen, Christoffer
Abstract : Personalized medicine or individualized therapy promises a paradigm shift in healthcare. This is particularly true in complex and multifactorial diseases such as diabetes and the multitude of related pathophysiological complications. Diabetic cardiomyopathy represents an emerging condition that could be effectively treated if better diagnostic and, in particular, better therapeutic monitoring tools were available. In this study, we investigate the ability to differentiate low and high doses of metabolically targeted therapy in an obese type 2 diabetic rat model. Low‐dose dichloroacetate (DCA) treatment was associated with increased lactate production, while no or little change was seen in bicarbonate production. High‐dose DCA treatment was associated with a significant metabolic switch towards increased bicarbonate production. These findings support further studies using hyperpolarized [1‐ 13 C]‐pyruvate magnetic resonance imaging to differentiate treatment effects and thus allow for personalized titration of therapeutics. Abstract : Hyperpolarized 13 C‐pyruvate magnetic resonance spectroscopy (MRS) was utilized to visualize changes in substrate selection in rodent hearts following acute treatment with low or high dichloroacetate (DCA) concentrations in an obese type 2 diabetic rat model. DCA treatments altered the cardiac substrate selection in a concentration‐dependent way and thus support the use of hyperpolarized 13 C‐pyruvate MRS for therapeutic monitoring in the diabetic heart.